The Simon and Marie Jaglom Collection - Cohen, Olga; Feldmann, Ruth; Guralnik, Nehama; Jaglom, Henry; Omer, Mordechai; Yifat, Dorit (Tel Aviv : Tel Aviv Museum of Art, 1995)
Jongkind, Johan Barthold ; Cézanne, Paul ; Sisley, Alfred ; Boudin, Eugène Louis ; Pissarro, Camille ; Cross, Henri Edmond ; Monet, Claude ; Derain, André ; Bonnard, Pierre ; Chagall, Marc ; Modigliani, Amedeo ; Matisse, Henri ; Liebermann, Max ; Gris, Juan ; Leger, Fernand ; de Vlaminck, Maurice
biografie, bibliografie
The Simon and Marie Jaglom Collection, Simon and Marie Jaglom Pavillion for Impressionist and Post-Impressionist Art, Tel Aviv Museum of Art, Tel Aviv, 1995
Engels & Hebreeuws
kunstcatalogus